1983
DOI: 10.1136/hrt.49.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial ball valve thrombus. Treatable cause of clinical deterioration in a patient with mitral stenosis.

Abstract: SUMMARY A 74 year old woman with mixed mitral valve disease presented with episodes of loss of consciousness and fainting. The attacks were noted to be closely related to posture, especially crouching, and this, with the clinical finding that the radial pulse disappeared before she lost consciousness, suggested the diagnosis of a ball valve thrombus. Cardiac catheterisation confirmed the diagnosis but was followed by a fall in blood pressure necessitating emergency surgery. The only position in which the circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In patients with rheumatic mitral stenosis who develop a ball valve thrombus as a complication, atrial fibrillation is often present. [2][3][4] In contrast, our patient was in normal sinus rhythm, suggesting that ball valve thrombus can rarely develop in patients with normal sinus rhythm also. Clinically ball valve thrombus can produce symptoms of heart failure or embolic stroke , peripheral embolism or sudden death.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In patients with rheumatic mitral stenosis who develop a ball valve thrombus as a complication, atrial fibrillation is often present. [2][3][4] In contrast, our patient was in normal sinus rhythm, suggesting that ball valve thrombus can rarely develop in patients with normal sinus rhythm also. Clinically ball valve thrombus can produce symptoms of heart failure or embolic stroke , peripheral embolism or sudden death.…”
Section: Discussionmentioning
confidence: 97%
“…Till date, less than 60 cases have been reported till the 1980's. [2][3][4] In most of the patients presenting with a ball valve thrombus, severe mitral stenosis of rheumatic origin has been the most common predisposing condition. Our patient had severe mitral stenosis and moderately severe aortic stenosis of rheumatic origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ball valve thrombus physiologically behaves like critical mitral stenosis with an acute rise in left atrial pressure secondary to severe mitral inflow obstruction, passive pulmonary venous congestion, pulmonary edema with subsequent paroxysmal nocturnal dyspnea, and orthopnea, as noted in our patient. Besides rheumatic mitral valve disease, ball valve thrombus has been noted in degenerative mitral valve disease [ 4 ], restrictive cardiomyopathy, and post-cardiac surgery, especially prosthetic mitral valve in situ. Right atrial ball valve thrombus is a rare event to be reported in prolonged parenteral nutrition with an intrajugular central line in situ.…”
Section: Discussionmentioning
confidence: 99%